Tissue-specific requirement of sodium channel and clathrin linker 1 (Sclt1) for ciliogenesis during limb development - Lee, Hankyu; Moon, Kyeong-Hye; Song, Jieun; Je, Suyeon; Bok, Jinwoong; Ko, Hyuk Wan (Frontiers in Cell and Developmental Biology, 2022)
Primary cilia have essential roles as signaling centers during development and adult homeostasis. Disruption of ciliary structure or function causes congenital human disorders called ciliopathies. Centriolar distal appendage (DAP) proteins are important for anchoring cilia to the membrane. However, the exact functions of DAP during in vivo ciliogenesis and animal development remain poorly understood. Here, we showed that the DAP component sodium channel and clathrin linker 1 (Sclt1) mutant mice had abnormal craniofacial and limb development with postnatal lethality. In mutant embryos, most of the affected tissues had defects in DAP recruitment to the basal body and docking to the membrane that resulted in reduced ciliogenesis and disrupted hedgehog (Hh) signaling in limb bud mesenchymal cells. However, limb digit formation and ciliogenesis in Sclt1 mutant mice were differentially affected between the fore- and hindlimb buds. The forelimbs developed normally in Sclt1 mutants, but the hindlimbs had preaxial polydactyly. Heterozygous loss of Cep83, another core DAP component, in Sclt1 mutant mice, caused forelimb and hindlimb polydactyly. These findings revealed the tissue-specific differential requirement of DAPs. Taken together, these results indicated that during limb development the ciliary base components, DAPs, play an essential role in ciliogenesis and Hh signaling in vivo in a position-dependent manner.